Strength and Durability Studies on Geopolymer Recycled Aggregate Concrete - Saravanakumar, P (International Journal of Engineering and Technology, 2018)
This paper aims to study the engineering and durability properties of fly ash-based geopolymer recycled aggregate concrete and the results were presented in this paper. The addition of recycled coarse aggregate (RCA) retrieved from construction and demolition(C&D) wastes showed promising function in construction industry as an alternative to natural aggregates. It conserves enormous quantities of natural resources and reduces the space required for the landfill disposal of C&D wastes. In this study an increment of 25% partial replacements by weight of natural aggregates with recycled aggregates in geopolymer concrete up to 100% replacements were studied. The concrete containing virgin aggregate and ordinary Portland cement was consider as control concrete and the results of geopolymer recycled aggregate concrete (GP-RAC) Â were compared with this. The fresh and mechanical properties of all the above four concrete mixes has been investigated. Results indicated that workability of geopolymer concrete decreases than control concrete and it took more than 24 hours to set. Geo polymer based recycled aggregate concrete exhibits better strength and durability performance than ordinary recycled aggregate concrete.Â Â